Performance appraisal in primary education institutions and research - Kocabaş, Nazlı Aykurt (My University, 2004)
İlköğretim dünyanın birçok ülkesinde devlet tarafından halka verilen en önemli hizmetlerden biri olarak görülür. Önemli bir konu olarak eğitim büyük bir özenle planlanır, uygulanır ve teftiş edilir. Çoğu ülkede öğretmenlerin değerlendirilmesi teftişle yapılır. Her kültürün uygun bir eğitim sistemine ve buna uygun bir değerleme sistemine sahip olması gerekliliği şüphe götürmez. Çalışmamızda ilköğretim öğretmenlerinin kurumlarındaki performans değerlendirme kavramını ve uygulamalarını destekleyip desteklemedikleri ve daha etkin hale gelmesi için bazı değişikliklere ihtiyaç duyup duymadıkları sorularının cevapları aranmıştır. Araştırmamızın temel amacı ilköğretim öğretmenlerinin performanslarının değerlendirilmesiyle ilgili inançlarını araştırmaktı. Araştırmanın sonucundan anlıyoruz ki araştırmamıza katılan öğretmenlerden çoğunluğu dahil oldukları performans değerlendirme sisteminde bazı değişiklikler olması fikrini desteklemektedirler. Primary Education is considered as one of the most important services which is given to public by governments in most countries all over the world. As an important issue, education is planned, applied and inspected with a great intention and care. In most countries evaluation, appraisal of teachers is made through the inspections. It is doubtless that each society must have an appropriate education system and appropriate appraisal system related with the education system. In our study we aimed to find out the answer of the question, whether public primary school teachers support their organizations' performance appraisal concept and practices or they need any changes in order to make it more efficient. Main purpose of our research was to investigate the beliefs of primary school teachers on the appraisal of their performances. From the result of the research we understand that, a great majority of the teachers who participated our research support the idea of making some changes in the performance appraisal system in which they are included and also they believe that the changes which can be done according to their opinions, would increase effectiveness of performance appraisal system used in Turkish Primary Education Institutions.
Keywords: İnsan Kaynakları